Is crime cointegrated with income and unemployment?: A panel data analysis on selected European countries - Baharom, A.H.
This paper examines the causality between income, unemployment and crime in 11 European countries employing the panel data analysis for the period 1993-2001 for both aggregated (total crime) and disaggregated (subcategories) crime data. Fixed and random effect models are estimated to analyze the impact of income and unemployment on total crime and various disaggregated categories of criminal activities. Hypothesis tests show that random effect model should be used for all (namely total crime, motor vehicle crime, domestic burglary, and violent crime) except for drug trafficking. Our results indicate that both income and unemployment have meaningful relationship with both aggregated and disaggregated crime. Crime exhibits positive significant relationship with income for all the categories except for domestic burglary, whereby it is significantly negative relationship. Crime also shows positive significant relationship with unemployment except for violent crime, whereby it is significantly negative relationship. The results also show strong country specific effect in determining the crime level.income; unemployment; crime; Europe; panel data analysis